QUality improvement in primary care to prevent hospitalisations and improve Effectiveness and efficiency of care for people Living with coronary heart disease (QUEL): Protocol for a 24-month cluster randomised controlled trial in primary care - Redfern, J.; Hafiz, N.; Hyun, K.; Knight, A.; Hespe, C.; Chow, C.K.; Briffa, T.; Gallagher, R.; Reid, Christopher; Hare, D.L.; Zwar, N.; Woodward, M.; et al. (2020)
Background: Cardiovascular disease (CVD), including coronary heart disease (CHD) and stroke, is the leading cause of death and disability globally. A large proportion of mortality occurs in people with prior CHD and effective and scalable strategies are needed to prevent associated deaths and hospitalisations. The aim of this study is to determine if a practice-level collaborative quality improvement program, focused on patients with CHD, reduces the rate of unplanned CVD hospitalisations and major adverse cardiovascular events, and increases the proportion of patients achieving risk factor targets at 24 months.